Forming the foundation of banking supervision on post-soviet space - B. M. Dzhuraev; M. Kurbonalizoda (Вестник Российского экономического университета имени Г. В. Плеханова)
The article investigates theoretical foundations of the banking supervision. The authors research simultaneously history of establishing the banking system starting from the 17th century and finishing with the period, when CIS countries got independence. Periods of establishing the banking supervision on post-soviet space were analyzed. The essence of the banking supervision from the juridical and economic points of view was presented. The authors on the basis of existing literature analysis and taking into account the mentioned approaches and norms of effective legislation formulated the definition of the banking supervisionin conformity with the banking system of post-soviet countries: banking supervision is one of the key functions of the Central Bank connected with observation, response, control and regulation, including identification and correction of demands and minimization of the totality of banking risks in order to guarantee protection of creditors and depositors, security and stability of the banking system. The authors came to the conclusion that in spite of raising quality of the banking supervision in post-soviet countries in general, the gradual shift to the international standards of accounting (MSFO) and standards of risk assessment (Basel I, Basel II, Basel II.5 and Basel III) the main problem is still the vulnerability of supervision and regulation models that are capable of early response, timely threat identification and use of preventive measures.